Des gestions contrastées des difficultés des élèves en classe - Laure Sochala; Sylvain Broccolichi (Éducation et Socialisation)
In view of the observation that the difficulties of pupils and teachers in French schools are on the increase, as noted in numerous research studies and evaluations, we are part of the field of research that seeks to identify the obstacles at play and potential levers based on surveys carried out in classes. Based on pre-existing results, we have chosen to study mainly the pedagogical strategies that condition the deployment or inhibition of interactive dynamics favouring the removal of misunderstandings or misunderstandings underlying the pupils’ difficulties. To this end, we took into consideration the situations of interaction (including at a distance), the tools used, the postures and movements of the teachers which in turn condition the activities, the initiatives taken and the (in)understandings of the pupils. The analyses resulting from this work confirm the limited, and sometimes even counter-productive, impact of the current use of digital tools. They also encourage us to extend this work with research on the training paths and conditions of practice according to which teachers’ pedagogical dispositions are constructed.